Global distribution and drivers of language extinction risk - Amano, Tatsuya; Sandel, Brody; Eager, Heidi; Bulteau, Edouard; Svenning, Jens-Christian; Dalsgaard, Bo; Rahbek, Carsten; Davies, Richard G.; Sutherland, William J. (Proceedings of the Royal Society. B, Biological sciences, 2014)
Many of the world's languages face serious risk of extinction. Efforts to prevent this cultural loss are severely constrained by a poor understanding of the geographical patterns and drivers of extinction risk. We quantify the global distribution of language extinction risk—represented by small range and speaker population sizes and rapid declines in the number of speakers—and identify the underlying environmental and socioeconomic drivers. We show that both small range and speaker population sizes are associated with rapid declines in speaker numbers, causing 25% of existing languages to be threatened based on criteria used for species. Language range and population sizes are small in tropical and arctic regions, particularly in areas with high rainfall, high topographic heterogeneity and/or rapidly growing human populations. By contrast, recent speaker declines have mainly occurred at high latitudes and are strongly linked to high economic growth. Threatened languages are numerous in the tropics, the Himalayas and northwestern North America. These results indicate that small-population languages remaining in economically developed regions are seriously threatened by continued speaker declines. However, risks of future language losses are especially high in the tropics and in the Himalayas, as these regions harbour many small-population languages and are undergoing rapid economic growth.